If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 15 = 12x + 3 Reorder the terms: 15 + 8x = 12x + 3 Reorder the terms: 15 + 8x = 3 + 12x Solving 15 + 8x = 3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 15 + 8x + -12x = 3 + 12x + -12x Combine like terms: 8x + -12x = -4x 15 + -4x = 3 + 12x + -12x Combine like terms: 12x + -12x = 0 15 + -4x = 3 + 0 15 + -4x = 3 Add '-15' to each side of the equation. 15 + -15 + -4x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -4x = 3 + -15 -4x = 3 + -15 Combine like terms: 3 + -15 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| 5y+6=2y+9 | | 39+6x+6=x^2+2x | | z=X-51/8 | | -11(-9)= | | 3a+2[2+39a-1]=2(3a+4) | | z=41-51/8 | | Log(8)x+2log(8)2=2 | | Log(8)+2log(8)2=2 | | -6-4x=6(1-7x)+4x | | x^2-4x+4+56=x^2 | | 35-3v=4v | | 43=4x+3 | | 6(6x-1)+4x=5x+50 | | q+7=8q+14 | | a(4a-15)=25 | | .45x+.05(14-x)=.10(71) | | 49x^2+28x+2=0 | | 2+-2=20 | | 10a=6a+36 | | x^4=x^4-8x^3+24x^2-32x+56+6 | | 4(-5)+(-5)+8=-32-3(-5) | | x^4=x^4-8x^3+24x^2-32x+56 | | -28a+21=-35 | | 15954a+1690b+1043c=127830000 | | a+b+c=25900 | | 36-9r=r*r | | 2n-1=8191 | | =6.5-0.83t | | 64=.5(x^2+8x) | | 7-6x=7+5x+5x | | =6.5t-0.83t^2 | | f(x)=5x^3+8x^2-4x^4 |